2012
DOI: 10.9721/kjfst.2012.44.4.441
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Properties and DPPH Radical Scavenging Ability of Sword Bean (Canavalia gladiata) Extract

Abstract: We investigated the chemical properties and antioxidant activities of sword bean (SWB) and compared it to soybean (SB) and black soybean (seoritae, BSB). The value of vitamin C, vitamin A, crude fat, and crude protein in SWB was 25.5, 0.37 mg/kg, 1.2, and 25.6%, respectively. The crude fat content (1.2%) in SWB was very low in comparison with those of SB (16.5%) and BSB (16.1%). In 16 free amino acids investigated, the histidine content (9.2%) was high in SWB, followed by SB (3.0%) and BSB (2.9%). Total flavon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 11 publications
1
9
0
1
Order By: Relevance
“…Cho et al [34] showed that the extraction yield of sword beans was highest in water at 17.6%, while the extraction yield in ethanol was very low at 0.1%. Kim et al [31] reported the highest value of 24.8% for hot-water extraction of sword beans and only 2.4% for ethanol extraction, which is very similar to the results of the present research. Therefore, the extracting range for < 53 μm particles with water for solvent is the most efficient, and measurement of functional properties was performed with extracts of roasted sword beans according to extraction conditions.…”
Section: Extraction Yieldsupporting
confidence: 91%
“…Cho et al [34] showed that the extraction yield of sword beans was highest in water at 17.6%, while the extraction yield in ethanol was very low at 0.1%. Kim et al [31] reported the highest value of 24.8% for hot-water extraction of sword beans and only 2.4% for ethanol extraction, which is very similar to the results of the present research. Therefore, the extracting range for < 53 μm particles with water for solvent is the most efficient, and measurement of functional properties was performed with extracts of roasted sword beans according to extraction conditions.…”
Section: Extraction Yieldsupporting
confidence: 91%
“…Recent studies suggested that legumes are abundant in natural antioxidants, and the 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical-scavenging activity of sword bean was higher than that of α-tocopherol [3,4]. The nutritious seeds of red sword bean (RSB, Canavalia gladiata (Jacq.)…”
Section: Introductionmentioning
confidence: 99%
“…12 It has recently been reported that sword beans may exhibit antioxidant activity that eliminates free radicals and protects against oxidative stress. 13 Soybean paste containing sword beans exhibits higher antioxidant activity and greater angiotensin-converting enzyme (ACE) inhibitory effects than other soybean pastes. 14 Chang et al (2013) 15 reported that the antioxidant activity and tyrosinase inhibitory effects of fermented Gochujang (hot pepper paste) with 10% sword bean were 1.2-fold and 1.1-fold higher, respectively, than that of normally fermented Gochujang.…”
Section: Introductionmentioning
confidence: 99%